IMPROVING THE ACCURACY OF INERTIAL-SATELLITE NAVIGATION SYSTEM IN IMMOBILITY MODE - K. V. Kozadaev; A. E. Makarenko (Informatika)
A method of improving the accuracy of navigation solutions in immobility mode between motion phases for loosely coupled inertial-satellite system with MEMS sensors is proposed. The method is based on invariance of the dynamic system state while stationary. The test results show the decrease of variation in estimation of geographical coordinates and velocities, and the increase of accuracy of determining the pitch and roll angles for dynamic systems, as well as the lack of increase of the course error.